Can Leaders Prevent Technology From Backfiring? Empowering Leadership as a Double-Edged Sword for Technostress in Care - Bauwens, Robin; Denissen, Marith; Van Beurden, Jeske; Coun, Martine (Frontiers in Psychology, 2021)
Purpose – Recent studies have called for more contextual studies of technostress and the role leaders can have in this experience. While technostress is an increasingly prevalent and severe phenomenon in care professions, limited studies have addressed its potential negative consequences for employee well-being and quality of care delivered in this sector or, more importantly, examined how the adverse consequences of technostress could be mitigated. Therefore, the present study addresses this gap by investigating how technostress in childcare affects quality of care delivered via emotional exhaustion and what influence empowering leadership plays in this relationship. Design/methodology approach - Incorporating the views of 339 Dutch childcare workers, this study tests a model in which technostress influences quality of care delivered, mediated by emotional exhaustion and moderated by empowering leadership. Findings - Results confirm that techno-invasion and techno-overload predict higher emotional exhaustion and lower quality of care delivered among childcare workers. Empowering leadership reduced the influence of techno-invasion on emotional exhaustion but strengthened the influence of techno-overload. Originality/value - Our results provide childcare organizations with relevant information on the increasing use of ICT that influences both childcare workers’ well-being and quality of care they deliver. Important implications are suggested for leadership geared at stimulating employees’ responsibility and accountability for different dimensions of technostress.